Industrial clusters development and organisation model - Palčič , Iztok (Anali PAZU, 2022)
Industrial clusters have been a prevalent element of several national competitiveness policies for the last 15 years The author of this paper has followed the birth, organisation and performance of industrial clusters in Slovenia and Austria for the period of three years. Based on several in-depth case studies in Slovenia and Austria I have built a cluster development and organisation model applicable to smaller (transitional) countries. I have identified factors that have an impact on cluster development and organisation at the level of general business environment. At the same time I have identified a government role in fostering clusters. But external factors are not the only factors influencing clusters. There are also internal factors that are in the hands of the cluster actors. These are factors that directly influence cluster development and organisation process. I have classified them in four areas and they will be also presented in this paper. I have also identified four stages of cluster birth, organisation and growth. The model is highly applicable as it combines research results with best practices based on several case studies.